Dynamic Parameters of Jet Electrodeposition for Ni-P Alloy - Wang, Y.; Kang, M.; Jin, S.W.; Fu, X.Q. (Asian Journal of Chemistry, 2014)
To study the electrochemical dynamic law in the process of jet electrodeposition for Ni-P alloy, the coating was prepared with self-developed device on the 45 carbon steel substrate. The influence of process parameters including the electrolyte temperature, dipolar space and electrolyte flow velocity on the dynamic parameters was examined by the potential sweep method. The experimental results show that within the range of experiments, the electrolyte temperature had small impact on the reversibility of the system, while the polarization resistance decreased with the increasing electrolyte temperature. The dipolar space had little effect on the reversibility of the system and the polarization resistance first decreased and then increased with the increase of dipolar space. The electrolyte flow velocity displayed the greatest impact on the reversibility of the system, meanwhile the polarization resistance increased with the increase of electrolyte flow velocity.